ID: 2. Issue 1 (November 2015) - Conrad, Curdin; Domizio, Jeremy Di; Mylonas, Alessio; Belkhodja, Cyrine; Demaria, Olivier; Navarini, Alexander; Lapointe, Anne-Karine; French, Lars; Vernez, Maxime; Gilliet, Michel
<x xml:space="preserve">Abstract</x> Paradoxical psoriasis is a well-known side-effect of anti-TNF therapy affecting 2–5% of treated patients. As this side effect often necessitates cessation of the anti-TNF therapy, there is an urgent need to understand its pathogenesis. Here, we analyzed a series of 25 cases of paradoxical psoriasis induced by all anti-TNF agents available. Underlying diseases, clinical presentation and histological patterns varied considerably among patients. However, we found a striking, uniform, and selective upregulation of type I interferons (IFN) in skin of paradoxical psoriasis as compared to classical psoriasis. The overexpression of type I IFN was paralleled by a massive accumulation of plasmacytoid dendritic cells (pDCs) within the skin. In-vitro, TNF blockade directly enhanced type I IFN production by pDCs, while TNF itself inhibited its production suggesting a crossregulation of TNF and pDC-derived type I IFN. In a skin injury mouse model, anti-TNF therapy increased and sustained type I IFN expression and skin infiltration by pDCs and was sufficient to induce a psoriatic phenotype in a type I IFN-dependent manner. Our study demonstrates that anti-TNF therapy unleashes unabated type I IFN production by pDCs, thereby inducing a psoriasis-like skin phenotype. Thus, we unravel the pathomechanism of paradoxical psoriasis and provide a clinical relevance for the crossregulation of TNF and type I interferon.